2008
DOI: 10.18002/pec.v0i7.696
|View full text |Cite
|
Sign up to set email alerts
|

Encontrando al Kaizen : un análisis teórico de la mejora continua

Abstract: Desde que Masaaki lmai acuño el término de Kaizen a mediados de los años ochenta, este se ha visto como un elemento clave para la competitividad de las empresas japonesas. No obstante, y a pesar de que el Kaizen ha sido definido por el autor que condujo a la luz el término, todavía sigue existiendo en la literatura sobre el tema cierta ambigüedad e inconsistencia. Además, existe una clara necesidad de desarrollar esta teoría en el campo de la dirección de operaciones.El propósito de este trabajo es analizar el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
1
11
0
4
Order By: Relevance
“…Some examples of theoretical studies are Bhuiyan et al (2006), Suárez-Barraza (2008), Suárez-Barraza et al (2011), Singh and Singh (2009, 2012 or Dahlgaard-Park et al (2013). However, among the analysed studies we have not found papers that, combining qualitative and quantitative analysis, review the evolution of the continuous improvement field.…”
Section: Introductionmentioning
confidence: 92%
“…Some examples of theoretical studies are Bhuiyan et al (2006), Suárez-Barraza (2008), Suárez-Barraza et al (2011), Singh and Singh (2009, 2012 or Dahlgaard-Park et al (2013). However, among the analysed studies we have not found papers that, combining qualitative and quantitative analysis, review the evolution of the continuous improvement field.…”
Section: Introductionmentioning
confidence: 92%
“…According to Cooney and Sohal (2004), teams that generate clear policies and standards achieve success. In addition, Barraza and Dávila (2009) state that a fundamental CI principle is to standardize operations in order to sustain the obtained achievements. 10.…”
Section: Continuous Improvement Sustainabilitymentioning
confidence: 99%
“…The Berger’s (1997) classification mentions two dimensions: individual or group tasks and a parallel structure or one that is integrated into daily work. According to Suárez-Barraza and Miguel-Dávila (2008), the Western aspect of Kaizen presents four practical applications: Kaizen blitz, Gemba-Kaizen workshops, office Kaizen and Kaizen teian (suggestion systems). Kaizen teian is the backbone of our research in its teamwork aspect, and operates according to three main principles: first, a participation system, in which employees participate voluntarily to improve their work; second, developing skills where it is the management’s responsibility to train employees at all times, and it is the employees’ responsibility to learn through practice; and third, creating a driving force, made up of top management policies, managers’ participation, developing objectives and reward mechanisms, preferentially not financial one (Japan Human Relations Association, 1992).…”
Section: Theoretical Frameworkmentioning
confidence: 99%